Phylogenetic Analysis of the Plant U2 snRNP Auxiliary Factor Large Subunit A Gene Family in Response to Developmental Cues and Environmental Stimuli - Lu, Shuai; Gao, Cong; Wang, Yongzhou; He, Yingying; Du, Junrong; Chen, Moxian; Zhao, Hua; Fang, Hui; Wang, Baohua; Cao, Yunying (Frontiers in Plant Science, 2021)
Splicing in all organisms is carried out through the formation of spliceosome complexes. Splicing auxiliary factors are required during the splicing process. U2AF65 is an extremely important splicing cofactor, and the two typical RRMs in the center of U2AF65 recognize and bind to the polypyrimidine sequence located between the intron branch site and the 3' splice site. U2AF65A is a member of U2AF65, and current research shows that it plays an important role in diseases of mammals, especially humans; however, few studies have investigated U2AF65A in plants, and its specific functions are poorly understood. In this study, we conducted comprehensive research to systematically identify U2AF65A in plant species from algae to flowering angiosperms. Phylogenetic analyses were followed by basic bioinformatics analyses, such as comparisons of the gene structure, protein domains, promoter motifs, and gene expression levels, including 113 putative U2AF65A sequences from 33 plant species. In addition, we took the model crop rice as the research object and showed that OSU2AF65A is a protein located in the nucleus. Rice U2AF65A participates in the response to various stressors, such as drought, high salt, low temperature, and the heavy metal cadmium. Our results provide the general characteristics of this gene family and will serve as a reference source for the functional study of the essential U2AF65A-specific splicing cofactor in the plant kingdom.